Productivity of high-oleic sunflower when grown in the conditions of the Southern Steppe of Ukraine - Kachanova, Tetiana; Manushkina, Tetiana; Petrova, Olena; Shevchuk, Natalia (Вісник аграрної науки Причорномор'я, 2023)
In modern agricultural systems, the basis of cultivation technology and an important factor determining the yield and quality of high-oleic sunflower seeds is regulation of mineral fertilizer rates. Therefore, the determination of their influence on the productivity of the culture determines the relevance of the conducted research. The purpose of the study is to determine the optimal rates of mineral fertilizer application to increase the yield of high-oleic sunflower hybrids in non-irrigated conditions of the Southern Steppe of Ukraine. To achieve the goal, a field study was conducted in the fields of the Mykolaiv State Agricultural Research Station of the Institute of Irrigated Agriculture of the National Academy of Agrarian Sciences of Ukraine. The subjects of the study are high-oleic sunflower hybrids Kadet, Hektor and Oplot, the originator of which is the V.Ya. Institute of Plant Breeding. Yuryev of the National Academy of Agrarian Sciences of Ukraine. As a result of the study, it was found that when applying N90P90K60, the Kadet hybrid formed the largest diameter of the basket - 19.5 cm, under the same feeding conditions, the diameter of the basket in the Hektor and Oplot hybrids was 14.3 cm and 16.4 cm, respectively. The largest mass of 1000 seeds for the level of N90P90K60 fertilization was established in the hybrid Cadet – 59.8 g, and at the level of fertilization N30P40K30 the lowest mass of 1000 seeds – 41.7 g was formed in the hybrid Hector. In addition, in the high-oleic sunflower hybrid Kadet, the content of crude fat in seeds and oleic acid in oil was the highest compared to other hybrids in all variants of fertilization. The application of mineral fertilizers also affected the yield of high-oleic sunflower, so the yield of the Kadet hybrid was 24.1% higher with the application of N90P90K60, compared to the variant of application of N30P40K30, and the yield of the Hektor and Oplot hybrids was 33.3% and 28%, respectively, which makes it possible to state that the level provision of mineral fertilizers helps to increase crop productivity. The obtained results provide an opportunity to improve the technology of growing high-oleic sunflower under conditions of insufficient moisture, and the perspective of further research may be to study the effect of increased norms of each individual macroelement or their joint effect on the productivity and quality of the high-oleic sunflower crop